Optimizing the Development of Prototype Learning Mode of Professional Ability Consolidation (PKP) Courses of the PGSD-UT Study Program in the Archipelago Region (Faculty of Teacher Training and Education, Universitas Terbuka, 2022)
Every semester, Professional Capability Consolidation (PKP) courses are always a scourge for Elementary School Teacher Education (PGSD) students of the Universitas Terbuka (UT). It is due to the lack of student knowledge of the procedures for implementing PKP courses and the limited skills of students in making practical reports. It affects their scores because they do not meet the minimum criteria, and students fail to pass the course. Especially during the pandemic, the implementation of practical courses that are usually held face-to-face is now all based on webinar tutorials. The learning process becomes more difficult for students living on islands with various limitations. This study aims to develop a prototype learning mode to overcome these problems with three main activities, including (1) making procedural video for implementing PKP courses of S1-PGSD, (2) training in writing PKP S1-PGSD UT reports, (3) assisting the undergraduate-PGSD students in the islands face-to-face. The study results show that it was necessary to develop advanced videos as a complement and elaborately detailed procedures for implementing the PKP courses for the students of S1-PGSD UT, the need for writing training with a greater number of meetings and writing practices, and the suitability of holding face-to-face mentoring of PKP courses for the students of S1-PGSD.